You can't catch me - McKenzie, Catherine (Lake Union Publishing, 2020)
"Twelve years ago Jessica Williams escaped a cult. Thanks to the private detective who rescued her, she reintegrated into society, endured an uncomfortable notoriety, and tried to put it all behind her. Then, at an airport bar, Jessica meets a woman with an identical name and birth date. It appears to be just an odd coincidence--until a week later, when Jessica finds her bank account drained and her personal information stolen. Following a trail of the grifter's victims, each with the same name, Jessica gathers players--one by one--for her own game. According to her plan, they'll set a trap and wait for the impostor to strike again. But plans can go awry, and trust can fray, and as Jessica tries to escape the shadows of her childhood, the risks are greater than she imagined. Now, confronting the casualties of her past, Jessica can't help but wonder... Who will pay the price?"--Provided by publisher.